"Fixing" climate change through carbon capture and storage: Situating industrial risk cultures. (September 2017) - Kuch, Declan
Highlights: Features original insights from ethnography of carbon capture pilot projects in Australia, including interviews with key policy proponents. Review of large CCS projects in Australia and USA shows reliance on government grant funding and Enhanced Oil Recovery contract revenue. Key finding is divergences between coal and oil industry expertise in worldviews and framing of risks to projects. Oil expertise has been crucial to framing CCS projects, including view of public as risk, which excludes constructive public participation. Understanding friction between industrial partners in CCS projects should help policymakers more easily confront the need to phase out fossil fuels and commensurate changes in infrastructure and lifestyles.